Identifikasi Mutasi Gen β Globin Ekson 1 Pada Pembawa Thalassemia - Satuti Nur Handayani, Niken; Tripramudya Onggo, Andika (Jurusan Biologi UIN Alauddin Makassar, 2014)
Thalassemia is an autosomal recessive genetic mutation disorder with symptoms similliar to anemia that causes deficiency synthesis of the globin chains (hemoglobin component inside erythrocytes). Thalassemia is classified based on secondary protein structure abnormalities in α globin protein or β globin protein. Based on data from Indonesian Thalassemia Foundation (YTI) in Indonesia, people with thalassemia, especialy β thalassemia is constantly increasing 8 to 10% per year, so it is very impotant to have a strategy that reduce the increasing number in the population. Genetic examination on the individual is very effective to detect quickly the person with thalassemia trait carrier, to reduce the number of thalassemia carrier population. Identification of 1st exon β globin gene mutations with sequencing method is one of the way to know the specific mutation in thalassemia carriers. Identification results can be used as a reference for the rapid detection of thalassemia trait carrier. This study aims to determine the type of mutation and location of nucleotide mutations in 1st exon β globin gene on carrier of thalassemia and the changes of amino acid translated by the mutant gene. The study was conducted by isolating the genome from the β thalassemia carrier blood, amplifying and sequencing the 1st exon β globin gene. The location of point mutation analysis and the changes of amino acid, was analyzed using computational method by comparative alignment using normal β globin gene as a comparison. The results of the research showed there is a point mutation in the 59th nucleotide caused by transition (T to C) and 147th nucleotide caused by transversion (G to C). The mutation type found on this study was a silent mutation because there is no change in the translated amino acid.Keywords: β globin, exon 1, mutation, thalassemia